Abutment connection structural changes in dual-retained and screw-retained metal-ceramic implant-supported restorations: an in vitro study, part I - Sareh Habibzadeh; Safoura Ghodsi; Marzieh Alikhasi; Seyed Ali Mosaddad; Hosein Mohebbi (BMC Oral Health)
Abstract Background This study sought to compare the rotational freedom and structural changes of abutment connections in dual-retained and screw-retained metal-ceramic implant restorations at different fabrication stages and following thermomechanical loading. Methods Twenty metal-ceramic restorations were equally divided into two groups. Group 1 (G1) consisted of dual-retained restorations on prefabricated titanium abutments, while Group 2 (G2) comprised screw-retained restorations on UCLA chromium-cobalt overcast abutments. Specimens underwent 500 cycles of thermocycling and 500,000 cycles of mechanical loading. Changes in connection dimensions and rotational freedom were compared within and between the groups before- and post-loading. Statistical analyses were conducted using a generalized linear model (GLM). The significance level was set at α = 0.05. Results Initially, no significant differences in connection dimensions were observed between the groups (P >.05). After loading, G2 exhibited significantly smaller hexagon side lengths and diagonal measurements, along with increased hexagonal angle deformation and concentricity (P <.001) compared to G1. Rotational freedom was significantly greater in G2 compared to G1 both before and after thermomechanical loading (P <.001). G2 experienced significant dimensional changes before and after loading (P <.001), whereas G1 showed no significant changes in connection dimensions pre- and post-loading (P >.05). Conclusions Dual-retained restorations outperformed screw-retained ones with minimal connection alteration and higher rotational stability.